1996
DOI: 10.1007/bf00168640
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a novel prolyl endopeptidase inhibitor, JTP-4819, on neuropeptide metabolism in the rat brain

Abstract: The effect of a novel prolyl endopeptidase (PEP) inhibitor, (S)-2-[[(S)-2-(hydroxyacetyl)-1-pyrrolidinyl] carbonyl]-N-(phenylmethyl)-1-pyrrolidine-carboxamide (JTP-4819), on neuropeptide metabolism was investigated in the rat brain. JTP-4819 exhibited a strong in vitro inhibitory effect on cortical and hippocampal PEP activity, with the IC50 values being approximately 0.58 +/- 0.02 and 0.61 +/- 0.06 nM, respectively. JTP-4819 also inhibited the in vitro degradation of substance P (SP), arginine-vasopressin (AV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 46 publications
0
35
1
Order By: Relevance
“…These findings do not support some earlier results [9,32], but we want to point out that a repeated treatment with S 17092 has also failed to increase the levels of brain neuropeptides [9]. A single oral administration of JTP-4819 did not increase thyrotropin-releasing hormone levels in rat cerebral cortex [33]. In aged rats, single administration of JTP-4819 failed to increase hippocampal substance P levels, and both cortical and hippocampal arginine-vasopressin levels remained unaffected after single or repeated JTP-4819 dosing [32].…”
Section: Discussioncontrasting
confidence: 82%
“…These findings do not support some earlier results [9,32], but we want to point out that a repeated treatment with S 17092 has also failed to increase the levels of brain neuropeptides [9]. A single oral administration of JTP-4819 did not increase thyrotropin-releasing hormone levels in rat cerebral cortex [33]. In aged rats, single administration of JTP-4819 failed to increase hippocampal substance P levels, and both cortical and hippocampal arginine-vasopressin levels remained unaffected after single or repeated JTP-4819 dosing [32].…”
Section: Discussioncontrasting
confidence: 82%
“…It is now firmly established that PEP plays a pivotal role in the catabolism of a variety of biologically active neuropeptides, notably those that appear to be implicated in memory and learning processes (Toide et al, 1996;Bellemère et al, 2003). Concurrently, it has been shown that selective PEP inhibitors exert antiamnesic effects and improve cognitive performances (Yoshimoto et al, 1987;Toide et al, 1995a), supporting the notion that PEP could be involved in the physiopathology of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 92%
“…In vitro studies have shown that PEP can actually cleave several neuropeptides, such as substance P (SP), ␣-melanocyte-stimulating hormone (␣-MSH), arginine-vasopressin (AVP), thyrotropin-releasing hormone (TRH), gonadotropin-releasing hormone (GnRH), neurotensin, and oxytocin, suggesting that PEP may contribute to peptide breakdown in the central nervous system (CNS; Taylor and Dixon, 1980;Wilk, 1983). In support of this hypothesis, it has been found that administration of PEP inhibitors provokes a significant increase in SP, ␣-MSH, AVP, and TRH concentrations in the rat brain (Toide et al, 1996;Bellemère et al, 2003).…”
mentioning
confidence: 82%
“…POP is implicated in the metabolism of peptide hormones and neuropeptides [2][3][4] although some of the previously identified neuropeptide substrates do not appear to be hydrolyzed in vivo upon closer inspection [5]. Specific inhibitors have been shown to relieve scopolamine-induced amnesia [6], to ameliorate memory loss caused by age, brain lesions, or amnesic drugs [7,8] and were neuroprotective under various conditions [9][10][11], resulting in significant pharmaceutical and academic interest. It was reported that POP has roles in the phosphoinositide cycle [12][13][14], intracellular transport [15], cellular differentiation [16], inflammation [17], angiogenesis [18], and cancer development [19].…”
Section: Introductionmentioning
confidence: 99%